2003
DOI: 10.1074/jbc.m209413200
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis Type I Tumor Suppressor Neurofibromin Regulates Neuronal Differentiation via Its GTPase-activating Protein Function toward Ras

Abstract: Neurofibromin, the neurofibromatosis type 1 (NF1) gene product, contains a central domain homologous to a family of proteins known as Ras-GTPase-activating proteins (Ras-GAPs), which function as negative regulators of Ras. The loss of neurofibromin function has been thought to be implicated in the abnormal regulation of Ras in NF1-related pathogenesis. In this study, we found a novel role of neurofibromin in neuronal differentiation in conjunction with the regulation of Ras activity via its GAP-related domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 40 publications
(52 reference statements)
1
79
0
3
Order By: Relevance
“…While NF1-associated pilocytic astrocytomas show loss and inactivation of NF1 alleles, sporadic pilocytic astrocytomas lack NF1 mutations or reduced NF1 expression (39). Neurofibromin, the gene product of NF1, is involved in the repression of MAPK signaling by its GTPase domain (12). Interestingly, while not detecting BRAF gene dupli- cations, Jones et al (10) identified a small copy number gain of the RAF1 locus at 3p25 in 1 pilocytic astrocytoma (10).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…While NF1-associated pilocytic astrocytomas show loss and inactivation of NF1 alleles, sporadic pilocytic astrocytomas lack NF1 mutations or reduced NF1 expression (39). Neurofibromin, the gene product of NF1, is involved in the repression of MAPK signaling by its GTPase domain (12). Interestingly, while not detecting BRAF gene dupli- cations, Jones et al (10) identified a small copy number gain of the RAF1 locus at 3p25 in 1 pilocytic astrocytoma (10).…”
Section: Figurementioning
confidence: 99%
“…Neurofibromin, the gene product of the NF1 gene, physiologically contributes to growth arrest of astrocytic cells and neuronal differentiation by downregulation of the MAPK signaling pathway via its GTPase-activating domain. Loss of neurofibromin expression conversely leads to increased Ras activity and astrocyte proliferation (12). Mutations of other components of the MAPK pathway cause several other inherited diseases, such as Noonan syndrome, LEOPARD syndrome, cardio-facio-cutaneous (CFC) syndrome, and Costello syndrome (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as we have shown previously, neurofibromin regulates neuronal differentiation via its GAP function. In PC12 cells, time-dependent increases in the GAP activity of cellular neurofibromin (NF1-GAP) were detected after nerve growth factor stimulation and were correlated with the down-regulation of Ras activity during neurite extension (6). Although cell migration and neurite extension are known to be regulated by cytoskeletal reorganization in cells, the molecular mechanisms by which neurofibromin is involved in these cytoskeletal dynamics are understood poorly.…”
mentioning
confidence: 99%
“…Although GAPs usually function to inactivate their cognate GTPase substrates, some are believed to function as effectors that mediate downstream signalingfor example, the RasGAP neurofibromatosis 1 (Yunoue et al, 2003) and TcGAP (Chiang et al, 2003). By contrast, some enhance the effect of the protein they interact with, such as the RhoGAP domain in the regulatory subunits of phosphoinositide 3-kinase, p85 (Zheng et al, 1994).…”
mentioning
confidence: 99%